Ammonia Oxidation at High Pressure as a Carbon Free Fuel - García Ruiz, Pedro; Abián, María; Alzueta, Uxue (Jornada de Jóvenes Investigadores del I3A, 2020)
Ammonia can be burned directly without pollutant emissions. Its mixtures with CH4 and H2 improve its combustion characteristics. Therefore, the project thesis is the knowledge of the conversion at high pressures of NH3 and its mixtures as well as the development of a suitable kinetic model.